The idea of the constitutional state and global society - A. Yeatman (Law Text Culture, 2004)
It is a commonplace observation that historically established modes of state formation are inadequately adapted to global social scale (see for example Kettl 2000; and for a theoretically sophisticated treatment of this issue Sassen 2000), although as we shall see this observation underestimates the dynamic by which this adaptation is currently occurring. Many commentators seem to conclude from the current lack of fit between the established type of state formation and global social scale that the state as such is not adequate to the demands of governing global society. This view conflates the two distinct dimensions of political organisation and social scale. Political organisation does have to be able to work with social scale, of that we can be certain, but the nature of their relationship is not one of containment. The state does not contain society, nor is it the role of the state to express society. Rather the role of the state is to provide the institutional order that brings society to account in relation to the procedural and substantive norms of justice. Units of political organisation do not have to match units of social organisation for there to be a relationship between them.